PENGARUH KUALITAS PELAYANAN,TERHADAP KEPUTUSAN MENGINAP ( Studi Pada Tamu Hotel Hasanah Jaya di Surabaya ) - Sofiah Nur Iradawati; WA Nur Dhuha Romadhana (Fakultas Ekonomi Universitas Yos Soedarso, 2020)
This research is motivated by the high growth rates of Semarang hotels that are imbalanced with the increase in the number of tourist. This certaintly will affect the number of visitor who stayed in a hotel. The hotel sevice provider must prepare the best strategy to attract consumers with the presence of the new hotel,because consumer of hotel become increasingly have many option to choose. Hotel Hasanah Jaya Surabaya is one of the hotels affected by these imbalances. Seen fron the data request to the hotel which had been steadily decrease since the year 2016 till 2020. The problem in this research is â€œ what is the factor that influence a person to staying in Hasanah Jaya Hotelsâ€. This specifically refers to three variables namely service quality, facillities and location. The purpose of this study was to examine the influence of these three vaiables in influencing the decission to stay at Hotel Hasanah Jaya Surabaya.After doing a literature review and preparation of hypothesis, data were collected through questionnaires to 90 guests of Hasanah Jaya Hotels obtain using sistematic sampling technique,Stay decission variables (Y), service quallity, facilities (X2) anf location (x3) testing the hypothesis using the t test showed that the three variables independent vaiables faound to sifnificantly influence the decission to stay as dependent variable. Then through the F test showed that the variable service quallity, facilities and location is appropriate to test the dependent variable decission to stay. Figures Adjusted R square of 0.473 shows that 47.3 percent of the variation can be explained by the three independent variables in the equation regression. While the other 52.7 percent is explained by other variables outside of the four variables used in this studyKeywords : Decission to Stay; Service Quality.